AMELIORATIVE EFFECTS OF Withania somnifera ROOT POWDER ON GROWTH PERFORMANCE OF CADMIUM TREATED CHICKENS1 (Indian Journal of Animal Production and Management, 2015)
A total of 90 chicks of one day age were divided randomly into five groups of 18 birds each viz. Group I (control), group II (100 ppm cadmium), group III (200 ppm cadmium), group IV (100 ppm cadmium + Withania somnifera root powder, WSRP) and group V (200 ppm cadmium + WSRP). Groups IV and V were administered WSRP orally in standard recommended feed at the rate of 1% concentration from 2 weeks of age till 60 days post treatment (DPT). Clinical signs, Body weight, feed consumption, body weight gain and feed conversion ratio were studied at 0, 15, 30, 45, 60 DPT. Birds in all the experimental groups were examined twice daily in morning and evening for recording of clinical manifestations, if any. Birds in groups I and IV were active, healthy and bright in appearance. In groups II and III, the birds showed decreased feed intake, weakness, lethargy, dullness and depression from 10th DPT upto 60th DPT. However, incoordination of movement was also observed in groups II and III from 30th DPT to 60th DPT. In group V, no other clinical signs were observed except dullness. There was dose and time dependent significant decrease in body weight, feed consumption, body weight gain but significant increase in feed conversion ratio. Withania somnifera, administered @ 1% in feed, in cadmium intoxicated birds @ 100 ppm and 200 ppm, minimized the adverse effects of cadmium.
Keywords: Withania somnifera; growth; performance; cadmium; chickens